Perancangan Aplikasi Pengadaan Aset Berbasis Web: Studi Kasus Pt. Xyz - Ryanda Argantara; Irfan Darmawan; Anwar Sadat (eProceedings of Engineering, 2017)
Abstrak – Asset procurement is an attempt to obtain goods or services, either from a third party or internally. This process can ensure a company will always have inventory on the assets needed to carry out its daily work. Procurement of assets at PT. XYZ is still experiencing some obstacles, such as the approval process and the delivery of procurement-related documents that often take a long time. Another problem is the number of documents printed and handled from the beginning of procurement to completion. These important documents are often piled up and messy, which makes Purchasing & Procurement unit staff able to make mistakes, such as document redundancy, missing documents, or documents that are still needed wasted with old documents. These problems can be solved by creating an electronic procurement system (eprocurement) through online so that it can be accessed anywhere and anytime, even data storage is better and regular. Application design method used is Waterfall method which is analyzed to existing business process first, system requirement analysis and user requirement, designing business process result of analysis, making and testing application. Testing is done by black box testing where the resulting output must be in accordance with the existing function. The asset procurement system is electronically built using ASP.NET language and SQL Server database. The results of this study is an online e-procurement system that has functionality in accordance with the results of design and analysis of the procurement process of existing assets at PT. XYZ. With e-procurement built is expected to facilitate and facilitate the procurement process in PT. XYZ. Keywords: asset, procurement, e-procurement